Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s00261-017-1138-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of fourth-generation iterative reconstruction algorithm with low-dose CT protocol in assessment of mesorectal fascia invasion in rectal cancer: comparison with magnetic resonance

Abstract: Low-dose protocol combined with iDose4 reconstruction algorithm offers high-quality images, obtaining significant radiation dose reduction, useful in the evaluation of MRF involvement in rectal cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For most CRC, CT is the routinely used imaging modality for tumor diagnosis, tumor staging, identifying patients who require neo-adjuvant therapy, and assessing treatment response [43][44][45][46]. Recently, some reports have found that new generation CT scanners can offer high spatial resolution images with reliable rectal staging with low dose of radiation, particularly useful in patients who have contraindication to MRI [47,48]. If used in conjunction with KRAS mutation status, CT may potentially be used as a noninvasive biomarker for deciding appropriate therapy selection and also predict patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…For most CRC, CT is the routinely used imaging modality for tumor diagnosis, tumor staging, identifying patients who require neo-adjuvant therapy, and assessing treatment response [43][44][45][46]. Recently, some reports have found that new generation CT scanners can offer high spatial resolution images with reliable rectal staging with low dose of radiation, particularly useful in patients who have contraindication to MRI [47,48]. If used in conjunction with KRAS mutation status, CT may potentially be used as a noninvasive biomarker for deciding appropriate therapy selection and also predict patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility to include with new CT scanner systems dose-intensive perfusion sequences in CT staging protocols without exceeding dose reference values is very encouraging given accuracy and validity of the perfusion analysis. Given the fact, that there are even attempts of the CT community to overtake T staging 36 which is to date clearly regarded as the holy grail of MR in rectal cancer imaging, the idea of a one-stop-shop CT approach in rectal cancer patients quickly comes to one’s mind. However, as dose recommendations for standard CT examinations are constantly updated and national CT dose reference values have been only recently lowered dramatically 22 , 37 , further optimization of perfusion CT protocols taking e.g.…”
Section: Limitationsmentioning
confidence: 99%